Implementasi Nilai Pancasila Dalam Mewujudkan Toleransi Kepada Penyandang Disabilitas - Leny Leny; Musfiroh Musfiroh; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to examine whether people in Indonesia have implemented the values of Pancasila in realizing tolerance for people with disabilities. In reality, as we know, there are still many cases of discrimination against people with disabilities, there is still a lack of availability of special facilities for people with disabilities, and weak law enforcement. The research method used is a qualitative method. By using literature review data collection techniques by reviewing various literature such as articles and journals that are relevant to the topic of discussion, as well as using interview techniques. It is hoped that the results of this research can increase insight and understanding of the implementation of Pancasila values in realizing tolerance for people with disabilities so that we are able to become a society that is tolerant towards people with disabilities and can provide support in the form of participation, as well as disseminating information through social media in realizing the importance of tolerance towards people with disabilities.